2015
DOI: 10.1128/aac.01476-15
|View full text |Cite
|
Sign up to set email alerts
|

Eagle Effect in Nonreplicating Persister Mycobacteria

Abstract: We determined the microbicidal activities of antibacterials against nonreplicating Mycobacterium smegmatis grown in a starvation-based Loebel model for persistence. Whereas most drugs lost their activity, fluoroquinolones retained lethal potency. Dose-response characterizations showed a paradoxical more-drug-kills-less Eagle effect. Pretreatment of cultures with chloramphenicol blocked the lethal action of the gyrase inhibitors. These results suggest that fluoroquinolones at low concentrations trigger a protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…For three of the five genes tested, we found that CAM caused increased mRNA stability under hypoxia. This is consistent with CAM’s mechanism of action and published work (5961). CAM inhibits elongation by preventing peptidyl transfer (6264) and causing ribosomal stalling (65).…”
Section: Resultssupporting
confidence: 92%
“…For three of the five genes tested, we found that CAM caused increased mRNA stability under hypoxia. This is consistent with CAM’s mechanism of action and published work (5961). CAM inhibits elongation by preventing peptidyl transfer (6264) and causing ribosomal stalling (65).…”
Section: Resultssupporting
confidence: 92%
“…The exposure to the two fluoroquinolones ciprofloxacin and ofloxacin, and the aminoglycoside gentamicin produce an increasing number of persisters above 0.15, 0.5, and 0.75 µg/mL, respectively. Examples of an in vitro more-drug-kills-fewer Eagle effect include vancomycin against C. difficile [ 155 ] and fluoroquinolones against M. smegmatis [ 156 ]. An in vivo model illustrated this effect in C. diphtheriae treated with amoxicillin [ 157 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, this loss of activity could be due to an Eagle effect of PAβN. The phenomenon has been described as a paradoxical effect of drugs where more drug kills less and apparently is not related to solubility 40,41 .…”
Section: Discussionmentioning
confidence: 99%